ND AND SR ISOTOPIC GEOCHEMISTRY OF MAFIC LAYERED INTRUSIONS IN THE EASTERN BALTIC SHIELD: IMPLICATIONS FOR THE EVOLUTION OF PALEOPROTEROZOIC CONTINENTAL MAFIC MAGMAS - Amelin Y.V.; Semenov V.S. (My University, 1996)
Nd and Sr isotopic data are presented for the 2449–2441 Ma Olanga and Burakovka layered mafic complexes in the eastern Baltic Shield. These complexes have similar tectonic position, but differ in two aspects: the age of the enclosing crust and the post-crystallization metamorphic history. The Sm–Nd isotopic results for the Kivakka and Lukkulaisvaara intrusions, Olanga Complex, are consistent with the model of closed-system crystallization of a single magma without significant wallrock assimilation. The Rb–Sr systems of minerals were disturbed by late Rb addition during 1.75–1.50 Ga metamorphism. The Nd and Sr isotopic systems in the Burakovka complex show no metamorphic disturbance and indicate mixing of at least four isotopically distinct components. Isotopic variations in the Burakovka Complex can be explained by a 4–20 per cent contamination of a primary komatiitic or picritic magma with a Mesoarchean crust, similar to that exposed in the region. A similar model, applied to the Olanga Complex using a Neoarchean crustal isotopic composition, cannot reproduce the observed isotopic signature. The nearly uniform initial ɛNd values between −1 and −2.3, observed in the Kivakka and Lukkulaisvaara intrusions of the Olanga Complex, as well as in the other 2.50–2.44 Ga layered mafic intrusions throughout the eastern Baltic Shield, are better explained by a mantle plume model with small amounts of crustal contamination and minor involvement of asthenospheric material. This model is also consistent with the geological observations and the temporal distribution of the Paleoproterozoic mafic magmatism in the eastern Baltic Shield. As an alternative, the enriched isotopic characteristics may be explained by melting of a metasomatically modified lithospheric mantle source.
Keywords: Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская